Atrial fibrillation in Retinal Artery Occlusions - Melanahalli, Shreyas; Tran, Tommy; Ng, Clement; Agrawal, Devendra K. (Cardiology and Cardiovascular Medicine, 2025)
Retinal artery occlusions, encompassing central retinal artery occlusion and branch retinal artery occlusion, are acute vascular events that can result in significant and often irreversible vision loss. These ocular emergencies are closely associated with systemic vascular risk factors, including hypertension, diabetes mellitus, advanced age, and cardiovascular comorbidities. Atrial fibrillation (AFib), the most common sustained cardiac arrhythmia, has emerged as a notable contributor to the risk of retinal artery occlusions. The prevalence of AFib is rising, particularly among older adults, paralleling the age-dependent increase in retinal artery occlusion incidence. Recent studies indicate a significant association between AFib and retinal artery occlusions, with AFib conferring an elevated risk for both retinal and cerebral ischemic events. Notably, Patients with retinal artery occlusion exhibit a heightened risk of subsequent AFib, stroke, and thromboembolic complications. The pathophysiological interplay involves embolic phenomena originating from cardiac or carotid sources, with AFib facilitating thrombus formation and embolization to the retinal circulation. Diagnostic advances, including prolonged cardiac monitoring and optical coherence tomography, have improved detection of both AFib and retinal ischemic changes. Despite the lack of a universally accepted treatment for retinal artery occlusions, early interventions such as thrombolysis and hyperbaric oxygen therapy may improve visual outcomes if administered promptly. This manuscript underscores the importance of comprehensive cardiovascular evaluation in patients with retinal artery occlusion, particularly for AFib, to optimize risk stratification, guide management, and reduce the likelihood of recurrent vascular events. Enhanced awareness and interdisciplinary collaboration are critical to improving prognosis and preventing further morbidity in this high-risk population.